HTLV-1 p12 modulates the levels of prion protein (PrPC) in CD4+ T cells - Silva De Castro, Isabela; Granato, Alessandra; Mariante, Rafael Meyer; Lima, Marco Antonio; Leite, Ana Claudia Celestino; Espindola, Otávio de Melo; Pise-Masison, Cynthia A.; Franchini, Genoveffa; Linden, Rafael; Echevarria-Lima, Juliana (Frontiers in Microbiology, 2023)
Infection with human T-cell lymphotropic virus type 1 (HTLV-1), is endemic in Brazil and is linked with pro-inflammatory conditions including HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), a chronic neuroinflammatory incapacitating disease that culminates in loss of motor functions. The mechanisms underlying the onset and progression of HAM/TSP are incompletely understood. Prior studies have demonstrated that inflammation and infectious agents can affect the expression of cellular prion protein (PrPC) in immune cells. Here, we investigated whether HTLV-1 infection affected PrPC content in cell lines and primary CD4+cells in vitro. We found that HTLV-1 infection decreased the expression levels of PrPC and HTLV-1 orf-I encoded p12, an Endoplasmic Reticulum resident protein also known to affect post-transcriptionally cellular proteins such as MHC-class I and the IL-2 receptor. In addition, we observed a reduced percentage of CD4+ T cells from infected individuals expressing PrPC, which was reflected by IFN type II but not IL-17 expression. These results suggested that PrPC downregulation, linked to both HTLV-1p12 and IFN- expression in CD4+ cells, may play a role in the neuropathogenesis of HTLV-1 infection.